Herpes simplex infections in atopic eczema. Issue 4 (April 1985) - David, T J; Longson, M
Abstract : One hundred and seventy nine children with atopic eczema were studied prospectively for two and three quarter years; the mean period of observation being 18 months. Ten children had initial infections with herpes simplex. Four children, very ill with a persistently high fever despite intravenous antibiotics and rectal aspirin, continued to produce vesicles and were given intravenous acyclovir. There were 11 recurrences among five patients. In two patients the recurrences were as severe as the initial lesions, and one of these children had IgG2 deficiency. Use of topical corticosteroids preceded the episode of herpes in only three of the 21 episodes. Symptomatic herpes simplex infections are common in children with atopic eczema, and are suggested by the presence of vesicles or by infected eczema which does not respond to antibiotic treatment. Virological investigations are simple and rapid: electron microscopy takes minutes, and cultures are often positive within 24 hours.